School-based intervention study examining approaches for well-being and mental health literacy of pupils in Year 9 in England: study protocol for a multischool, parallel group cluster randomised controlled trial (AWARE). Issue 8 (3rd September 2019) - Hayes, Daniel; Moore, Anna; Stapley, Emily; Humphrey, Neil; Mansfield, Rosie; Santos, Joao; Ashworth, Emma; Patalay, Praveetha; Bonin, Eva; Boehnke, Jan Rasmus; Deighton, Jessica
Abstract : Introduction: The prevalence of emotional difficulties in young people is increasing. This upward trend is largely accounted for by escalating symptoms of anxiety and depression. As part of a public health response, there is increasing emphasis on universal prevention programmes delivered in school settings. This protocol describes a three-arm, parallel group cluster randomised controlled trial, investigating the effectiveness and cost-effectiveness of two interventions, alongside a process and implementation evaluation, to improve mental health and well-being of Year 9 pupils in English secondary schools. Method: A three-arm, parallel group cluster randomised controlled trial comparing two different interventions, the Youth Aware of Mental Health (YAM) or the Mental Health and High School Curriculum Guide (The Guide), to Usual Provision. Overall, 144 secondary schools in England will be recruited, involving 8600 Year 9 pupils. The primary outcome for YAM is depressive symptoms, and for The Guide it is intended help-seeking. These will be measured at baseline, 3–6 months and 9–12 months after the intervention commenced. Secondary outcomes measured concurrently include changes to: positive well-being, behavioural difficulties, support from school staff, stigma-related knowledge, attitudes and behaviours, and mental health first aid. An economic evaluation will assess the cost-effectiveness of the interventions, and a process and implementation evaluation (including a qualitative research component) will explore several aspects of implementation (fidelity, quality, dosage, reach, participant responsiveness, adaptations), social validity (acceptability, feasibility, utility), and their moderating effects on the outcomes of interest, and perceived impact. Ethics and dissemination: This trial has been approved by the University College London Research Ethics Committee. Findings will be published in a report to the Department for Education, in peer-reviewed journals and at conferences. Trial registration number: ISRCTN17631228 . Protocol: V1 3 January 2019. Substantial changes to the protocol will be communicated to the trials manager to relevant parties (eg, ISRCTN).